THE USE OF SONG LYRICS TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Ningsih, Ningsih; Sofian, Sofian; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to improve students? vocabulary mastery of kindergarten one students of Town for Kids Preschool by using song lyrics. The method of this research is collaborative classroom action research. The researcher acted as the teacher and the class English teacher acted as the observer during the teaching and learning process. The research is conducted in three cycles. The instruments used to collect the data are observation checklist form, vocabulary checklist form and individual test checklist form.The result of the research shows improvement of the student? interest and understanding in  learning the vocabulary of body part. The second cycle is related to  the improvement of the student? respond and understanding in  learning the vocabulary in the song before. The third cycle is related to the improvement of the student? vocabulary mastery. The result of this research showed that the students? vocabulary mastery is improving a lot and it brings remarkable effects to the students? speaking ability. The use of song lyrics in teaching vocabulary to the preschooler help the students to learn and memorize the vocabulary and sentence structure faster and easier. Keywords: Song Lyrics, Improve, Vocabulary Mastery